Evaluasi Pekerjaan Geser Lengkung Jalur Kereta Api (Studi Kasus: Lengkung Nomor 11 Km 8+303 Sampai Km 8+484 Wonokromo Surabaya) - R Endro Wibisono; Ade Irma Irjayanti (Universitas Dr. Soetomo, 2023)
Planning railroad geometry is planned based on the speed of the train that will pass through the railroad. One of the railroad geometries is straight and curved roads or the horizontal alignment of railroads. The railroad track consists of straight lines and curved lines. The straight line allows trains to run according to operational speed. On a curved track, the train has the possibility of lowering its speed due to the condition of the curved track with a certain height and radius. Therefore, it is necessary to do a good job and in accordance with the work plan. The formulation of the problem of this research is how the data analysis techniques in curved shear work; what is the procedure for carrying out curved shear work; and what is the follow-up and the results of the implementation of the curved shift. The purpose of this study is to determine the impact of curved shear work on the motion of the train. This research method was carried out based on PD No. 10 of 1986 PT Kereta Api Indonesia (Persero). The research location is at arch number 11 KM 8+303 to 8+484 Wonokromo Surabaya. The curved shear work and bend inspection were carried out based on PT Kereta Api Indonesia (Persero) operational standards in 2019. From the curved shear work, it is planned to change the bend radius from 450 m to 350 m. The results of the inspection of the bends after the curved shearing work obtained a curved radius of 350 m, a height of 109, an average AP of 143 and a speed of 80 km/hour.